Photoelectron shake-ups as a probe of molecular symmetry: 4d XPS analysis of I3− in solution. Issue 30 (18th July 2018) - Norell, Jesper; Grell, Gilbert; Kühn, Oliver; Odelius, Michael; Bokarev, Sergey I.
Abstract : Accurate XPS simulations reveals the connection between solvent-induced nuclear asymmetry and shake-up intensity in the 4d spectra of I3 − . Abstract : A combination of multi-configurational restricted active space calculations with a Dyson orbital formalism has been applied for accurate simulations of 4d photo-electron spectra of the I3 − molecular ion. The analysis based on the occupation numbers of natural orbitals allowed to predict and rationalize the spectral fingerprints of solvent-induced nuclear asymmetry. In particular, it demonstrates how the nuclear asymmetry directly causes an increase of shake-up intensity. The relative intensity of shake-up and main features of the I 4d XPS spectrum could therefore serve as a simplified experimental observable of structural asymmetry, complementary to changes in the shape of the main spectral features.